Changing body structure components and motor skills in military high school students within one year - Glavač Boris; Dopsaj Milivoj; Đorđević-Nikić Marina; Maksimović Miloš; Marinković Marjan; Nedeljković Jasmina (Vojnosanitetski Pregled, 2015)
Background/Aim. Proper growth and development of adolescents in the morphological, functional and psychosocial aspects is the imperative of the educational process. The aim of this study was to determine the status and changes in the indicators of morphological characteristics, motor skills and lifestyle habits among the students of the Military High School in Belgrade. Methods. The study included 217 students aged 15 to 18 years (from the first to the fourth grade). The two measurements performed at the intervals of one year were used to determine: the body structure by means of 10 variables and motor skills by 4 variables, while life habits were determined by 25 variables. Results. The differences in the indicators of morphological characteristics were recorded in all the groups, being the highest in the first year of schooling. During the period of growing up, a reduction of fatty component in percentage values was found, as well as an increase of muscle mass. The progressive growth of motor skills in the first, second and the third grade was recorded in the manifestation of power, and endurance improved only in the first year. In terms of dietary habits, there was no difference among the groups. Conclusion. The obtained results indicate proper morphological and motor development and the formation of lifestyle habits. The data obtained will serve as a basis for health and functional prevention and upgrading in terms of improvement of the process of military education. [Projekat Ministarstva nauke Republike Srbije, br. III47015]